Thioredoxin and Glutaredoxin Systems as Potential Targets for the Development of New Treatments in Friedreich’s Ataxia - Marta Seco-Cervera; Pilar González-Cabo; Federico V. Pallardó; Carlos Romá-Mateo; José Luis García-Giménez (Antioxidants, 2020)
The thioredoxin family consists of a small group of redox proteins present in all organisms and composed of thioredoxins (TRXs), glutaredoxins (GLRXs) and peroxiredoxins (PRDXs) which are found in the extracellular fluid, the cytoplasm, the mitochondria and in the nucleus with functions that include antioxidation, signaling and transcriptional control, among others. The importance of thioredoxin family proteins in neurodegenerative diseases is gaining relevance because some of these proteins have demonstrated an important role in the central nervous system by mediating neuroprotection against oxidative stress, contributing to mitochondrial function and regulating gene expression. Specifically, in the context of Friedreich’s ataxia (FRDA), thioredoxin family proteins may have a special role in the regulation of Nrf2 expression and function, in Fe-S cluster metabolism, controlling the expression of genes located at the iron-response element (IRE) and probably regulating ferroptosis. Therefore, comprehension of the mechanisms that closely link thioredoxin family proteins with cellular processes affected in FRDA will serve as a cornerstone to design improved therapeutic strategies.